2007
DOI: 10.1523/jneurosci.2033-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Sialic Acid in Regulation of Neuronal and Network Excitability in the Rat Hippocampus

Abstract: The extracellular membrane surface contains a substantial amount of negatively charged sialic acid residues. Some of the sialic acids are located close to the pore of voltage-gated channel, substantially influencing their gating properties. However, the role of sialylation of the extracellular membrane in modulation of neuronal and network activity remains primarily unknown. The level of sialylation is controlled by neuraminidase (NEU), the key enzyme that cleaves sialic acids. Here we show that NEU treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 40 publications
10
87
0
2
Order By: Relevance
“…This desialylation leads to stabilization of channels in the plasma membrane, thereby increasing channel surface expression and ionic flux. In a second example, hippocampal network excitability is modulated by endogenous neuraminidase that removes external sialic acids (41). If similar mechanisms are involved in cardiomyocyte function, then extracellular glycosyltransferases/glycosidases would likely produce rapid adjustments to surface channel glycosylation.…”
Section: Two Mechanisms By Which Regulated Ion Channel Glycosylation mentioning
confidence: 99%
“…This desialylation leads to stabilization of channels in the plasma membrane, thereby increasing channel surface expression and ionic flux. In a second example, hippocampal network excitability is modulated by endogenous neuraminidase that removes external sialic acids (41). If similar mechanisms are involved in cardiomyocyte function, then extracellular glycosyltransferases/glycosidases would likely produce rapid adjustments to surface channel glycosylation.…”
Section: Two Mechanisms By Which Regulated Ion Channel Glycosylation mentioning
confidence: 99%
“…The negative charges on extracellular sialic acid residues of gangliosides contribute to membrane surface charge and may thus influence voltage-dependent properties of ion-channels (Green and Andersen, 1991). For instance, it has recently been shown that removal of sialic acid from the extracellular neuronal membrane by neuraminidase treatment shifts the activationand inactivation-voltage of Na + channels (Isaev et al, 2007), although it remains unclear whether removal of sialic acid from either the surrounding gangliosides or the ion-channel protein itself is causing this effect. The tendency for increased quantal content at 35 C at dKO compared to WT NMJs indicates that the presence of GM3 alone is not sufficient to keep quantal content at WT level.…”
Section: Temperature-dependencymentioning
confidence: 99%
“…Removal of Mg 2+ ions from extracellular solution shifts leftward the half activation and facilitates the amplitude of I Na compared with the 1mmol Mg 2+ solution [12].Our results suggest that the change in the surface charge dramatically affects the probability of induction of low-Ca 2+ SLA, providing evidence that Mg 2+ can reduce cerebral excitability by screening surface charge and support the idea that lack of Mg 2+ could cause epileptic seizures. In previous studies, it was shown that manipulations with surface charge could alter the pattern of epileptiform like activity [19]. In previous work we demonstrated that surface charge plays a crucial role in lowMg 2+ model of epilepsy [12].…”
Section: Resultsmentioning
confidence: 79%